The Effect of Compensation and Motivation on Employee Performance at Wai Tiddo Nature Tourism, Luwu Regency - Tauhid, Ananda Nurul; Saharuddin; Kasran, Muhammad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
In realizing an optimal level of performance, Wai Tiddo Nature Tourism has tried to do various things, such as improving employee discipline and simplifying every employee's work plan to facilitate task work and improve performance. This writing aims to determine the effect of compensation and motivation on employee performance in Wai Tiddo nature tourism, Luwu Regency. The research was conducted by disseminating the questionnaire, while the research method used simple random sampling. The study's results stated that compensation and motivation partially or simultaneously affected employee performance in Wai Tiddo Nature Tourism, Luwu Regency.